Body Composition and Metabolic Changes in a Lyon Hypertensive Congenic Rat and Identification of Ercc6l2 as a Positional Candidate Gene - Clark, Karen C.; Wagner, Valerie A.; Holl, Katie L.; Reho, John J.; Tutaj, Monika; Smith, Jennifer R.; Dwinell, Melinda R.; Grobe, Justin L.; Kwitek, Anne E. (Frontiers in Genetics, 2022)
Central obesity is genetically complex, and its exponential increase in the last decades have made it a critical public health issue. The Lyon Hypertensive (LH) rat is a well-characterized hypertensive model that also exhibits spontaneous and profound differences in body weight and adiposity, relative to its metabolically healthy control, the Lyon Normotensive (LN) rat. The mechanisms underlying the body weight differences between these strains are not well-understood, thus a congenic model (LH17LNa) was developed where a portion of the proximal arm of LN chromosome 17 is introgressed on the LH genomic background to assess the contribution of LN alleles on obesity features. Male and female LH17LNa rats were studied, but male congenics did not significantly differ from LH in this study. Female LH17LNa rats exhibited decreases in total body growth, as well as major alterations to their body composition and adiposity. The LH17LNa female rats also showed decreases in metabolic rate, and a reduction in food intake. The increased adiposity in the female LH17LNa rats was specific to abdominal white adipose tissue, and this phenomenon was further explained by significant hypertrophy in those adipocytes, with no evidence of adipocyte hyperplasia. Sequencing of the parental strains identified a novel frameshift mutation in the candidate gene Ercc6l2, which is involved in transcription-coupled DNA repair, and is implicated in premature aging. The discovery of the significance of Ercc6l2 in the context of female-specific adipocyte biology could represent a novel role of DNA repair failure syndromes in obesity pathogenesis.